2021
DOI: 10.3390/f12080969
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gonipterus Species and Their Egg Parasitoids in Australia: Implications for Biological Control

Abstract: Gonipterus species are pests of Eucalyptus plantations worldwide. The egg parasitoid wasp Anaphes nitens is used in many countries for the biological control of Gonipterus spp. Recent taxonomic studies have shown that the three invasive Gonipterus spp., which were previously considered as G. scutellatus, form part of a cryptic species complex. These taxonomic changes have implications for the biological control of Gonipterus spp. The aims of this study were to understand the species composition and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
4
0
6
Order By: Relevance
“…Commercial forest plantations require an assessment of the state of health of the tree stand in regard to the presence of insect pests and disease [50]. The eucalyptus weevil has for many years been controlled through the use of its parasitoid [51] with different results [52]. In spite of this, very few studies have evaluated its effects in eucalyptus stands.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial forest plantations require an assessment of the state of health of the tree stand in regard to the presence of insect pests and disease [50]. The eucalyptus weevil has for many years been controlled through the use of its parasitoid [51] with different results [52]. In spite of this, very few studies have evaluated its effects in eucalyptus stands.…”
Section: Discussionmentioning
confidence: 99%
“…cloelia phenology, temperaturedependent development and biology is crucial for the selection of appropriate and effective biological control agents. A number of studies have now concluded that biological control effectiveness relies on matching the parasitoid with its target species (Gerard et al 2021;Rowbottom et al 2013;Schröder et al 2021;Zilahi-Balogh et al 2012). As shown above, there are some prospects for advancing classical biological control of Pst.…”
Section: Biological Control (Conservation and Classical)mentioning
confidence: 99%
“…Damage by G. platensis is low in Australia because of the natural resistance of Eucalyptus species and the suppression of this pest by a diversity of natural enemies ( Valente et al, 2017 ; Valente et al, 2019 ; Afonso et al, 2019 ). However, this insect causes severe damage on exotic Eucalyptus species in some African, American, and European countries ( Reis et al, 2012 ; Souza et al, 2016 ; Valente et al, 2018 ; Schröder et al, 2020 ), resulting in a constant search for alternatives to control this pest ( Nascimento et al., 2017 ; Damascena et al, 2020 ; Schröder et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%